Activity Functional Outcome of Poor Prestroke Glycemic Control in Diabetic Patients with Acute Ischemic Stroke (Medical Forum Monthly, 2021)
Objective: Diabetes mellitus (DM) is an independent risk factor of cerebrovascular events including for ischemic stroke. In diabetic patients, prestroke glycemic control is known to impact the functional outcome of acute ischemic stroke. Therefore, we conduct this study to see the activity Functional outcome of poor Prestroke glycemic control in Diabetic patients with acute ischemic stroke.Study Design: A prospective, cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of Internal Medicine, Sandeman Provincial Hospital, Quetta from January till July 2014.Materials and Methods: All patients of diabetes mellitus type II admitted in the hospital with acute ischemic stroke were included. HbA1c levels were done and correlated with functional outcome of stroke. Data was entered and analyzed using SPSS v 19.0.Results: The study was completed by 136 patients. Their mean age was 53.2 ± 8.4 years. There were more males than females (60% vs. 40%). Hba1c was ≥10% in 82 (60.3%) patients. Poor functional outcome was reported in 94 (69.1%; p=0.000) patients. Poor functional outcome was statistically related to older age (≥40 years) (n=81; 86.2%), hypertension (n=68; 72.3%; p=0.000), smoking (n=54; 57.4%; p=0.01), and Hba1c ≥10% (n=69; 73.4%; p=0.000).Conclusion: In diabetic patients, the predictors of poor short term functional outcome of acute ischemic stroke include age ≥40 years, hypertension, smoking, and Hba1c ≥10%.